2007
DOI: 10.1111/j.0022-2879.2007.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Prudential Regulation and the “Credit Crunch”: Evidence from Japan

Abstract: The underlying causes of sharp declines in bank lending during recessions in large developed economies, as exemplified by the U.S. in the early 1990s and Japan in the late 1990s, are still being debated due to the lack of any convincing identification strategy of the supply side capital-lending relationship from lending demand. Using within bank share of real estate lending in the late 1980s as an instrumental variable for bank capital, we find that Japanese banks cut back on their lending in response to a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 34 publications
2
101
1
Order By: Relevance
“…Watanabe (2007) or Berrospide and Edge (2010) highlight the difficulties inherent in estimating target capital levels.…”
Section: Results 1 When the Capital Constraint Is Binding And The Desimentioning
confidence: 99%
See 4 more Smart Citations
“…Watanabe (2007) or Berrospide and Edge (2010) highlight the difficulties inherent in estimating target capital levels.…”
Section: Results 1 When the Capital Constraint Is Binding And The Desimentioning
confidence: 99%
“…Focusing on that later development, Woo (2003) and Watanabe (2007) found that Japanese banks significantly reduced their lending in response to a large increase in bank capital requirements resulting from the reinforcement of the prudential policy guidelines by the Japanese regulator. Watanabe's results suggest a very large role was played by the contraction of capital in business lending: had capital not been squeezed, business lending to sound industries (which indeed fell, depending on the industry, between 3 and 5 % points) would actually have increased.…”
Section: Bank Capital and Lending Growth: An Overview Of The Empiricamentioning
confidence: 99%
See 3 more Smart Citations